Retraction notice to “Exposure of adult zebrafish (Danio rerio) to SARS-CoV-2 at predicted environmentally relevant concentrations: Outspreading warns about ecotoxicological risks to freshwater fish” [Sci. Total Environ. 880 (2023) 163269] - Thiarlen Marinho da Luz; Abraão Tiago Batista Guimarães; Stênio Gonçalves da Silva Matos; Sindoval Silva de Souza; Alex Rodrigues Gomes; Aline Sueli de Lima Rodrigues; Edison Luiz Durigon; Ives Charlie-Silva; Ítalo Nascimento Freitas; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Abner Marcelino Silva; et al. (Science of The Total Environment, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Anti-respiratory syncytial virus and anti-herpes simplex virus activity of chemically engineered sulfated fucans from Cystoseira indica - Subrata Jana; Andre Luiz Dyna; Saikat Pal; Shuvam Mukherjee; Isabella Maria Tomaz Bissochi; Sueli Fumie Yamada-Ogatta; Maria Laura Goussain Darido; Danielle Bruna Leal Oliveira; Edison Luiz Durigon; Bimalendu Ray; Ligia Carla Faccin-Galhardi; Sayani Ray (Carbohydrate Polymers, 2024)

Genetic diversity of adenovirus in neotropical bats from Brazil - Laís Santos Rizotto; Larissa Mayumi Bueno; Thaís Camilo Corrêa; Maria Vitória dos Santos de Moraes; Amanda de Oliveira Viana; Laura Morais Nascimento Silva; Julia Cristina Benassi; Guilherme Pereira Scagion; Bruna Larotonda Telezynski Lopes; Isabela Barbosa de Assis; Tatiana Ometto; Erick Gustavo Dorlass; et al. (Brazilian Journal of Microbiology, 2023)

First report on the toxicity of SARS-CoV-2, alone and in combination with polyethylene microplastics in neotropical fish - Raíssa de Oliveira Ferreira; Abraão Tiago Batista Guimarães; Thiarlen Marinho da Luz; Aline Sueli de Lima Rodrigues; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Chinnasamy Ragavendran; Chinnaperumal Kamaraj; Ives Charlie-Silva; Edison Luiz Durigon; Helyson Lucas Bezerra Braz; Andrés Hugo Arias; et al. (Science of The Total Environment, 2023)

RETRACTED: Exposure of adult zebrafish (Danio rerio) to SARS-CoV-2 at predicted environmentally relevant concentrations: Outspreading warns about ecotoxicological risks to freshwater fish - Thiarlen Marinho da Luz; Abraão Tiago Batista Guimarães; Stênio Gonçalves da Silva Matos; Sindoval Silva de Souza; Alex Rodrigues Gomes; Aline Sueli de Lima Rodrigues; Edison Luiz Durigon; Ives Charlie-Silva; Ítalo Nascimento Freitas; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Abner Marcelino Silva; et al. (Science of The Total Environment, 2023)

Correction to: Potential outbreak by herpesvirus in equines: detection, clinical, and genetic analysis of equid gammaherpesvirus 2 (EHV-2) - Angélica Cristine de Almeida Campos; Sofia Cicolo; Cairo Monteiro de Oliveira; Camila Vieira Molina; Pedro Enrique Navas-Suárez; Thais Poltronieri dos Santos; Vanessa Barbosa da Silveira; Carla Meneguin Barbosa; Raquel Yvonne Arantes Baccarin; Edison Luiz Durigon; Luiz Gustavo Bentim Góes; Carla Bargi Belli; et al. (Brazilian Journal of Microbiology, 2023)

Potential outbreak by herpesvirus in equines: detection, clinical, and genetic analysis of equid gammaherpesvirus 2 (EHV-2) - Angélica Cristine de Almeida Campos; Sofia Cicolo; Cairo Monteiro de Oliveira; Camila Vieira Molina; Pedro Enrique Navas-Suárez; Thais Poltronieri dos Santos; Vanessa Barbosa da Silveira; Carla Meneguin Barbosa; Raquel Yvonne Arantes Baccarin; Edison Luiz Durigon; Luiz Gustavo Bentim Góes; Carla Bargi Belli; et al. (Brazilian Journal of Microbiology, 2023)

First detection of Psittacid alphaherpesvirus 5 and coinfection with beak and feather disease virus in naturally infected captive ringneck parakeets (Psittacula krameri) in Brazil - Roselene Ecco; Laura Morais Nascimento Silva; Maira dos Santos Carneiro Lacerda; Maria Vitória dos Santos de Moraes; Letícia Batelli de Oliveira; Willian Henrique de Magalhães Santos; Laís Santos Rizotto; Luís Henrique Gouvêa Saraiva; Larissa Mayumi Bueno; Erick G. Dorlass; Edison Luiz Durigon; Fernando Rosado Spilki; et al. (Archives of Virology, 2022)

Classification of new morbillivirus and jeilongvirus sequences from bats sampled in Brazil and Malaysia - Heather L. Wells; Elizabeth Loh; Alessandra Nava; Mónica Romero Solorio; Mei Ho Lee; Jimmy Lee; Jum R. A. Sukor; Isamara Navarrete-Macias; Eliza Liang; Cadhla Firth; Jonathan H. Epstein; Melinda K. Rostal; et al. (Archives of Virology, 2022)
As part of a broad One Health surveillance effort to detect novel viruses in wildlife and people, we report several paramyxovirus sequences sampled primarily from bats during 2013 and 2014 in Brazil and Malaysia, including seven from which we recovered full-length genomes. Of these, six represent the first full-length paramyxovirid genomes sequenced from the Americas, including two that are the first full-length bat morbillivirus genome sequences published to date. Our findings add to the vast number of viral sequences in public repositories, which have been increasing considerably in recent years due to the rising accessibility of metagenomics. Taxonomic classification of these sequences in the absence of phenotypic data has been a significant challenge, particularly in the subfamily Orthoparamyxovirinae , where the rate of discovery of novel sequences has been substantial. Using pairwise amino acid sequence classification (PAASC), we propose that five of these sequences belong to members of the genus Jeilongvirus and two belong to members of the genus Morbillivirus . We also highlight inconsistencies in the classification of Tupaia virus and Mòjiāng virus using the same demarcation criteria and suggest reclassification of these viruses into new genera. Importantly, this study underscores the critical importance of sequence length in PAASC analysis as well as the importance of biological characteristics such as genome organization in the taxonomic classification of viral sequences.

Lower cost alternatives for molecular diagnosis of COVID-19: conventional RT-PCR and SYBR Green-based RT-qPCR - Erick Gustavo Dorlass; Cairo Oliveira Monteiro; Amanda Oliveira Viana; Camila Pereira Soares; Rafael Rahal Guaragna Machado; Luciano Matsumiya Thomazelli; Danielle Bastos Araujo; Fabyano Bruno Leal; Erika Donizette Candido; Bruna Larotonda Telezynski; Camila Araujo Valério; Vanessa Nascimento Chalup; et al. (Brazilian Journal of Microbiology, 2020)

Divergent coronaviruses detected in wild birds in Brazil, including a central park in São Paulo - Carla M. Barbosa; Edison L. Durigon; Luciano M. Thomazelli; Tatiana Ometto; Roberta Marcatti; Marcello Shiavo Nardi; Daniel M. de Aguiar; João Batista Pinho; Maria Virginia Petry; Isaac Simão Neto; Patrícia Serafini; Roberta Costa Rodrigues; et al. (Brazilian Journal of Microbiology, 2019)

First detection of avian influenza virus (H4N7) in Giant Petrel monitored by geolocators in the Antarctic region - Elisa de Souza Petersen; Jansen de Araujo; Lucas Krüger; Marina M. Seixas; Tatiana Ometto; Luciano M. Thomazelli; David Walker; Edison Luiz Durigon; Maria Virginia Petry (Marine Biology, 2017)

A real-time RT-PCR for rapid detection and quantification of mosquito-borne alphaviruses - Marilia Farignoli Romeiro; William Marciel de Souza; Aline Lavado Tolardo; Luiz Carlos Vieira; Dyana Alves Henriques; Jansen de Araujo; Carlos Eduardo Hassegawa Siqueira; Tatiana Elias Colombo; Victor Hugo Aquino; Benedito Antonio Lopes da Fonseca; Roberta Vieira de Morais Bronzoni; Maurício Lacerda Nogueira; et al. (Archives of Virology, 2016)

Use of reverse transcriptase polymerase chain reaction (RT-PCR) in molecular screening of Newcastle disease virus in poultry and free-living bird populations - Adriano de Oliveira Torres Carrasco; Juliana Nogueira Martins Rodrigues; Meire Christina Seki; Fabricio Edgar de Moraes; Jaqueline Raymondi Silva; Edison Luis Durigon; Aramis Augusto Pinto (Tropical Animal Health and Production, 2013)

Rabies in southeast Brazil: a change in the epidemiological pattern - Luzia Helena Queiroz; Silvana Regina Favoretto; Elenice Maria S. Cunha; Angélica Cristine A. Campos; Marissol Cardoso Lopes; Cristiano de Carvalho; Keila Iamamoto; Danielle Bastos Araújo; Leandro Lima R. Venditti; Erica S. Ribeiro; Wagner André Pedro; Edison Luiz Durigon (Archives of Virology, 2012)

Phylogenetic analysis of a near-full-length sequence of an erythrovirus genotype 3 strain isolated in Brazil - Lilian Walsh Keller; Maria Luisa Barbosa; Fernando Lucas Melo; Lilian M. Pereira; Elias David-Neto; Luiz E. Lanhez; Edison Luiz Durigon (Archives of Virology, 2009)

Shape and size of red blood cells from the Pygoscelid penguins of Antarctica using atomic force microscopy - Cínthia C. Bonatto; Beatriz S. Magalhães; Joaquim O. Branco; Edison L. Durigon; Luciano P. Silva (Polar Biology, 2009)